Determinan Kejadian Anak Balita Gizi Buruk dan Gizi Kurang Usia 6-24 Bulan Pada Keluarga Non Miskin di Wilayah Kerja Puskesmas Rogotrunan Kecamatan Lumajang Kabupaten Lumajang - Sulistiyani, Sulistiyani; Listyowati, Lita Dwi; Ningtyias, Farida Wahyu (IKESMA, 2010)
This research is a qualitative study that analyzed the determinant factor is the occurrence of malnutrition among children under the age of 6-24 months of non-poor families in the working area Rogotrunan District Health Center Lumajang, Lumajang. The target of this research is the mother of a toddler, who has a child under five with poor nutrition or malnutrition 6-24 months of age on non-poor families as much as 8 informants. The samples taken by purposive. The results showed that characteristics of children under five who became the subject of research is mostly women. Although the nutritional status of all children under five in this study were malnourished and underweight but their weight at birth was normal, all born with a weight > 2500 grams. Spacing of all children under five with a brother or sister is more than 2 years, and nearly all children under five was the second child. The characteristics of mothers, the average education level is high, and most are workers. The level of nutrition knowledge of mothers is enough. Based on the informant in-depth interview study that parenting becomes a major determinant, although the level of higher education and high levels of maternal knowledge but in terms of child care that is the practice of exclusive breastfeeding and complementary breastfeeding is really not done well. In terms of time less than the maximum care and parenting than mothers who tend to be left to the maid or grandmother for informants who worked without any special attention by the mother also helped support the occurrence of malnutrition and undernourishment among the children. Key words: malnourished, underweight, non-poor family